Speech Prosody 2018 2018
DOI: 10.21437/speechprosody.2018-188
|View full text |Cite
|
Sign up to set email alerts
|

L1 Influence and Task effects in the realization of sentence types by Inuktitut-English sequential bilinguals

Abstract: This paper explores the role of cross-linguistic influence and task type in the realization of pitch accents and nuclear contours across English sentence types (statements, absolute questions and declarative questions) by sequential Inuktitut-English bilinguals. In Inuktitut, intonation is mainly a cue for phrasing; i.e., boundary tones are mapped to finality vs. continuity in turn-taking [1,2]. Questions are morphologically marked [3], and while a rising intonation may also be used, it is not always present. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…As mentioned in Section 3, research shows that, as it was the case with Cusco Quechua, bilinguals transfer prosodic patterns from Inuktitut to English, since differences were found in the perception and production of corrective focus (Colantoni et al 2014) when bilinguals were compared to monolinguals. Evidence of crosslinguistic influence in the realization of English statements, absolute yes/no questions, and declarative questions has also been reported recently (Colantoni et al 2018). This study, which included imitation of isolated sentences as well as production of the same sentence types in context, showed that Inuktitut-English bilinguals matched English monolinguals more closely in the realization of final contours than in the amount of pitch change observed in initial pitch accents.…”
Section: × √supporting
confidence: 69%
See 1 more Smart Citation
“…As mentioned in Section 3, research shows that, as it was the case with Cusco Quechua, bilinguals transfer prosodic patterns from Inuktitut to English, since differences were found in the perception and production of corrective focus (Colantoni et al 2014) when bilinguals were compared to monolinguals. Evidence of crosslinguistic influence in the realization of English statements, absolute yes/no questions, and declarative questions has also been reported recently (Colantoni et al 2018). This study, which included imitation of isolated sentences as well as production of the same sentence types in context, showed that Inuktitut-English bilinguals matched English monolinguals more closely in the realization of final contours than in the amount of pitch change observed in initial pitch accents.…”
Section: × √supporting
confidence: 69%
“…The literature on language contact and intonation supports this general prediction, since it has been found that sentence type and focus appear to be at different levels. There is evidence that prosodic marking of sentence type can be acquired by different types of bilinguals (Colantoni et al 2018;Marasco 2020;Zárate-Sández 2015) but prosodic marking of focus is rarely acquired (e.g., Ortega-Llebaria and Colantoni 2014;Nava and Zubizarreta 2010) or exhibits a protracted and gradual acquisition (Leal et al 2019). There is also the issue of which prosodic markers you are "choosing".…”
Section: Discussionmentioning
confidence: 99%